Peculiarities of the use of indirect costs allocation method, based on the assignment of indirect costs to departments - Tamulevičienė, Daiva; Mackevičius, Jonas; Liubinaitė, Ermina (Buhalterinės apskaitos teorija ir praktika, 2022)
No costing method can guarantee that cost accuracy will be 100% correct. This is primarily due to the problem of attributing indirect costs to the cost of a product or service. However, in recent decades, most of the research on the allocation of indirect costs has focused on Activity Based Costing (ABC) method, which is too complex and too costly for many companies. In contrast, research into the method of allocating indirect costs to departments has been unduly reduced. This method, often referred to as the traditional approach, is popular with the vast majority of companies and, if properly applied, would result in a reasonably accurate allocation of indirect costs to the cost of goods and services. The objective of the study is to reveal the peculiarities of the application of indirect cost allocation method based on the assignment of indirect costs to departments, with a view to improving the efficiency of the use of this method in the assignment of indirect costs to the cost of goods or services. The paper examines the peculiarities of the traditional method of allocating indirect costs, proposing not only a sequence for allocating these costs, but also the criteria for selecting the basis for the allocation of indirect costs, alternative methods of allocating indirect costs to production units, and the principles for calculating the indirect cost rate. All of this would allow enterprises to apply the indirect cost allocation method, based on assignment oh indirect cost to departments, much more effectively, both in financial accounting, for the purpose of determining cost of sales for the preparation of financial statements, and in management accounting, for the purpose of making various management decisions.